2013
DOI: 10.1021/ja3115746
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of Phosphate in Vanadium Phosphate Oxide for the Catalytic Activation and Functionalization of n-Butane to Maleic Anhydride

Abstract: We used density functional theory to study the mechanism of n-butane oxidation to maleic anhydride on the vanadium phosphorus oxide (VPO) surface. We found that O(1)═P on the V(V)OPO4 surface is the active center for initiating the VPO chemistry through extraction of H from alkane C-H bonds. This contrasts sharply with previous suggestions that the active center is either the V-O bonds or else a chemisorbed O2 on the (V(IV)O)2P2O7 surface. The ability of O(1)═P to cleave alkane C-H bonds is due to its strong b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
88
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 39 publications
1
88
0
Order By: Relevance
“…A long-standing puzzle was how a surface site could be active enough to break the strong butane C-H bond. Our previous two studies, denoted in this paper as CG 2,3 , used the Perdew-Burke-Ernzerhof 4 (PBE) flavor of density functional theory (DFT) with periodic boundary conditions (PBC) to investigate butane activation on (VO) 2 P 2 O 7 and on α 1 -, α 2 -, and X1-VOPO 4 . CG found that only the P=O motif on (VO) 2 P 2 O 7 α 2 -VOPO 4 α 1 -VOPO 4 X1-VOPO 4 5 the X1 phase could activate butane with a low activation barrier, E a = 13.6 kcal/mol.…”
Section: Introductionmentioning
confidence: 99%
“…A long-standing puzzle was how a surface site could be active enough to break the strong butane C-H bond. Our previous two studies, denoted in this paper as CG 2,3 , used the Perdew-Burke-Ernzerhof 4 (PBE) flavor of density functional theory (DFT) with periodic boundary conditions (PBC) to investigate butane activation on (VO) 2 P 2 O 7 and on α 1 -, α 2 -, and X1-VOPO 4 . CG found that only the P=O motif on (VO) 2 P 2 O 7 α 2 -VOPO 4 α 1 -VOPO 4 X1-VOPO 4 5 the X1 phase could activate butane with a low activation barrier, E a = 13.6 kcal/mol.…”
Section: Introductionmentioning
confidence: 99%
“…[3] This leads to Ea,min = 35.5 kcal/mol, better than those for the αI-and αII-VOPO4 surfaces, but still not reactive enough to lead to explain the experiments. [15] This leaves us in the untenable position that no V site on any of the reduced or oxidized surfaces of VPO can explain the observed activation of n-butane.…”
Section: Reactivity Of Vopo4 Toward N-butane C-h Activationmentioning
confidence: 88%
“…[2,3] We first focused on identifying the reaction center responsible for activating the methylene C-H bond of n-butane. Only the [001] surface of VOPO is considered, since experiments have suggested that it plays an important role in the catalysis.…”
Section: Reactivity Of Vopo Toward N-butane C-h Activationmentioning
confidence: 99%
See 2 more Smart Citations